Effect of Arbuscular Mycorrhizal Fungi, Selenium and Biochar on Photosynthetic Pigments and Antioxidant Enzyme Activity Under Arsenic Stress in Mung Bean (Vigna radiata) - Alam, Mohammad Zahangeer; McGee, Rebecca; Hoque, Md. Anamul; Ahammed, Golam Jalal; Carpenter-Boggs, Lynne (Frontiers in Physiology, 2019)
Environmental perturbations alter biochemical compounds in food crops. Arsenic (As), a toxic metalloid, is known to affect the cultivation of food crops in many regions of the world; however, the changes in chlorophyll, catalase (CAT), and proline in response to As stress and the role of stress relief substances remain largely unknown in mung bean (Vigna radiate L.). In this study, biochar (BC), arbuscular mycorrhizal fungi (AMF), and selenium (Se) were applied to soils as stress relief substances (under 30 mg kg-1 As stress), and the effects of BC, AMF, and Se on chlorophyll a, chlorophyll b, total chlorophyll, CAT activity, and proline content were studied in different mung bean genotypes. Under As stress, the chlorophyll a, chlorophyll b, and total chlorophyll contents in BARI mung 3, BARI mung 5, and BARI mung 8 were found statistically similar. Meanwhile, CAT activity increased in comparison to the control due to the application of BC, AMF, and Se in mung bean crops. However, proline was found significantly lower in AMF, BC, and Se-treated mung bean. This indicates that oxidative stress was potentially minimized in As-stressed mung bean crops due to the application of these stress relief substances. Notably, AMF was relatively effective against As stress in comparison to BC and Se. It is concluded that BC, AMF, and Se are all highly effective in enhancing antioxidant defenses as well as the nutritional quality of mung bean crops under As stress.